An explanation of the pathogenesis of several autoimmune diseases in immuno‐compromised individuals. (16th November 2020) - Roe, Kevin
Abstract: Some pathogen infections and immune system deficiencies have been linked to a few autoimmune diseases. However, the pathogenesis of most autoimmune diseases is unknown. An explanatory hypothesis for the pathogenesis of infection‐initiated autoimmune diseases is provided. Virulent pathogen infections create extensive pathogen antigens that frequently require antibodies. These antibodies create extensive antigen‐antibody immune complexes, which some immuno‐compromised individuals will not adequately eliminate. This will cause inflammatory type III hypersensitivity symptoms, including protease releases that destroy epithelium, mesothelium and endothelium basement membranes, express new immunogenic antigens from previously sequestered basement membrane constituents, and ultimately induce new autoantibodies. This can continue after the infection ends, if the first wave of protease attacks on basement membranes induces new autoantibodies that cause new uncleared antigen‐antibody immune complexes and type III hypersensitivity reactions. The secreted proteases and other enzymes will have preferred substrates and these proteases or other enzymes by themselves, or by their processed protein substrates, can express immunogenic antigens that induce new autoantibodies and initiate various autoimmune diseases. In summary, several autoimmune diseases can be initiated in immuno‐compromised individuals during extensive pathogen infections, if these individuals have two immune problems: (a) slow or weak initial immune responses that result in a reliance on antibodies and (b) an inability to eliminate the resulting antigen‐antibody immune complexes by phagocytosis. These two immune problems and the resulting immune system type III hypersensitivity reaction can explain the causation of several autoimmune diseases, including the most common and the rarest autoimmune diseases, both their differences and their similarities.